Exploring the psychological determinants of household's intention to reduce food waste: Insight from Yogyakarta Indonesia - Anggrasari, Herdiana; Cahyasita, Dhika; Ridwan, Muhamad (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Food waste's negative effects on the environment and monetary losses have made it a major concern. Food waste at the consuming stage has been directly affected by customer purchasing behaviour. Moreover, the majority of food waste happens within households. This means examining the reasons behind household food waste behaviour is a potential safeguard against food waste issues. This research aimed to analyze household food waste behavior in the Special Region of Yogyakarta after the COVID-19 pandemic. This study was conducted with a questionnaire survey from June to July 2023 to households in the Yogyakarta Special Region. Data was collected purposively using online and offline methods simultaneously. A total of 245 responses were obtained, and 203 were valid for use. Partial Least Square Structural Equation Modeling (PLS-SEM) was used as the analytical method. The research results showed that psychological factors such as attitudes, perceived behavioral control, emotions, moral beliefs, and knowledge about food management influenced households' intentions to reduce food waste. By examining the factors that affect food waste, it is hoped that this research will advance our understanding of trends in food waste behavior at the household consumer level in developing nations.